Community corrections - Gunnison, Elaine (Carolina Academic Press, 2017)
Community corrections : historical development & current trends--student learning outcomes -- Assessment : offenders' placement in the system -- Profile of community corrections offenders and specialized populations -- Probation : historical overview & current status -- Intermediate sanctions : other alternatives -- Parole : historical overview & current status -- Juveniles in the community corrections mix -- Reentry -- Challenges and obstacles -- Promising reentry interventions -- Revocation of probation or parole -- The unsung heroes : community corrections officers -- Finding their place : ex-offenders fight to regain a place in society -- Looking ahead : the future trends in community corrections